Cost-efficient reconfigurable geometrical bus interconnection system for many-core platforms - Tirumale Ramesh; Khalid Abed (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
System-on-chip (SoC) embedded computing platforms can support a wide range of next generation embedded artificial intelligence and other computationally intensive applications. These platforms require cost effective interconnection network. Network-on-chip has been widely used today for on-chip interconnection. However, it is still considered expensive for large system sizes. As full bus-based interconnection has high number of bus connections, reduced bus connections might offer considerable implementation economies with relatively small design cost for field programmable gate arrays (FPGAs) based embedded platforms. In this paper, we propose a cost efficient generalized reconfigurable bus-based interconnection for many-core system with reduced number of bus connections. We generalize the system with b =min {n,m}/k number of interconnect buses in which where n is the number of processor cores, m is the number of memory-modules and k is the general bus reduction factor. We present four geometrical interconnect configurations and provide their characterization in terms of memory bandwidth, cost per bandwidth and bus fault tolerance for various system sizes. Our results show that these configurations provide reduced cost per bandwidth and can achieve higher system throughput with bus cache.